PENGARUH SERTIFIKASI HALAL, KEPERCAYAAN KONSUMEN, DAN KUALITAS INFORMASI DIGITAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK HALAL DI E-COMMERCE PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ABDURRAB PEKANBARU - Endah Wahyuningsih; M Filbert Musnal; Budi Satria (Jurnal Ekonomi Bisnis Kompetif, 2026)
Abstract. The growth of e-commerce has transformed consumer behavior regarding the purchase of halal products; consequently, halal certification, consumer trust, and digital information quality have become critical factors influencing purchasing decisions. This study aims to analyse consumer perceptions of these three factors in the context of purchasing halal products via e- commerce. A quantitative approach was employed, utilizing, asurvey method involving 114 respondents who had previously purchased halal products online. Data were collected using a five-point Likert scale questionnaire and analyzed through descriptive statistics. The results indicate that all variables fell into the “very high” category. The halal certification variable achieved the highest mean score at 4,63 (92,54%), followed by purchasing decision at 4,36 (87,11%), digital information quality at 4,25 (84,96%), and cosumer trust at 4,20 (84,04%). These findings demonstrate that consumers hold highly positive perceptions regarding the presence of halal certifikatin, the quality of digital information, and the level of trust involved in e-commerce transactions. Halal certification received the highestrating, indicating that the guarantee of halal status is a primary consideration when purchasing halal products online. However, as the current findings are descriptive in nature, they do not explain the causal relationships between the variables. Therefore, further research utilizing inferential analysis is required to empirically examine the influence of halal certification, consumer trust, and digital information quality on puchasing decisions.